To nie jest muza. Rola klientki w domu Rietveld Schröder - Friedman, Alice T.; Lipiński, Filip (Artium Quaestiones, 2025)
This text is a translation into Polish of an essay that is a case study of Rietveld Schröder House, an important work of modern architecture in Utrecht, the Netherlands. The text was originally published as “Not a Muse: The Client’s Role at the Rietveld Schröder House”, in: The Sex of Architecture, eds. D. Agrest, P. Conway, L.K. Weisman, New York 1996, pp. 217–232 and its different version was republished as a chapter in Friedman’s book Women and the Making of the Modern House (Harry N. Abrams, 1998). The essay brings to the fore the active role of its female patron, Truus Schröder, in the designing the house, shifting the canonical narratives focusing on the celebrated male architect Gerrit Rietveld, and purely formal aspects of architectural design. While this is a study of an individual project, it can serve as a template for reconsidering other collaborations of this kind between female patrons and architects, as well as the gendered aspects of architectural design.